Assessment of Growth and Survival Rate of Plantations under the PUNCAMPA Scheme of the Ropar Division - Singh, Vedpal; Kaur, Amanpreet; Hussain, Mohit; Chauhan, Nitesh (Indian Forester, 2024)
Monitoring and analysis of the project helps to determine whether it was worth the investment or if there are better ways to accomplish things. Punjab government assigned the Forest Research Institute (FRI), Dehradun to monitor and evaluate the Punjab Forest Department's CAMPA activity. To meet the scheme's objectives, planting must be regularly monitored and reviewed in Ropar Division. GPS-assisted survey was conducted at each of the sites to confirm the area. Forest Research Institute, Dehradun observed and analyzed PUNCAMPA(2019-22) three-year plantations between February and March 2023 at the studies allocated areas. Representative sample plots were randomly chosen in all Forest Ranges. Monitoring locations included are 100% of the plantation's area and 10% of each sample site. Maximum height and collar diameter was recorded in Tectona grandis (3.10 m, 5.45 cm) in 2019-20 plantation, Pongamia pinnata (1.89 m, 4.10 cm) in 2020-21 and Pongamia pinnata recorded highest collar diameter (4.63 cm) and Acacia catechu having maximum height (2.93 m) in 2021-22 plantation. Highest Survival Percentage was found in Nurpur Bedi range in all three years plantation ie 74.03% in 2019-20, 73.19% in 2020-21 and 74.51 in 2021-22 followed by Ropar and Shri Chamkaur Sahib Range. Thus, this monitoring and evaluation will aid policymakers and State Forest Department in their decision-making for better plantation measures for their future management.